HYBRID KITOSAN/BENTONIT SEBAGAI MATRIKS UNTUK PELEPASAN ION AMONIUM DALAM AIR - Bambang Piluarto; Yusril Ihza Mahendra; Novita Andarini (Universitas Airlangga, 2016)
AbstrakHybrid kitosan/bentonit dalam bentuk bead telah berhasil dibuat dengan berbagai rasio komposisi kitosan dan bentonit. Dalam penelitian ini, bead dari hybrid ini digunakan sebagai matriks untuk ion amonium. Bead dibuat dengan pengendapan suspensi kitosan dan bentonit menggunakan koagulan NaOH. Bead hybrid yang diperoleh dikarakterisasi daya serap air (DSA) dan pelepasan ion amonium dalam air. Hasil yang diperoleh menunjukkan bahwa bentuk bead dipengaruhi oleh kandungan bentonit dalam hybrid. Peningkatan kandungan bentonit dalam hybrid menurunkan nilai DSA, namun meningkatkan pelepasan ion amonium dalam air. Sisa basa pada permukaan bead hybrid mempengaruhi deteksi pelepasan ion amonium dalam air. Kata kunci: hybrid, bead, suspensi, daya serap air, pelepasan ion AbstractChitosan/bentonite hybrid in the form of beads was successfully prepared in various of chitosan and bentonite composition ratio. In this study, beads of hybrid play role as matrix for ammonium ions. Beads prepared by precipitation of chitosan and bentonite suspension using NaOH as coagulant. Characterization beads obtained were carried out on water uptake and release of ammonia ions in the water. The results showed that forms of bead were affected by bentonite content in the hybrid. Increasing of bentonite content decreased water uptake of hybrid, however the release of ammonia ions in the water increased. Remaining base in the beads surface affected detection of release of ammonia ions in the water. Keywords: hybrid, beads, suspension, water uptake, release of ions